On order of elements in hypergroups and p-Sylow subhypergroups. Issue 12 (2nd December 2017) - Jantani, F.; Jafarpour, M.; Mousavi, S. Sh.; Leoreanu, V.
ABSTRACT: In this paper we define a left order, right order and order of an element in a hypergroup, which has a left scalar identity, right scalar identity and scalar identity, respectively. Using left and right orders, we define and investigate some classes of subhypergroups, especially p -Sylow subhypergroups of a hypergroup. Moreover, some examples have been proposed to show that the Sylow theorems do not hold for polygroups.